Three-particle motion under gravity in Stokes flow: an equilibrium for spheres in contrast to "an end-of-world" for point particles - Ekiel-Jeżewska, M.L.; Wajnryb, E. (Archives of Mechanics, 2006)
Evolution of three identical solid spheres falling under gravity in a low-Reynolds number flow is investigated for a symmetric initial configuration. Three spheres aligned horizontally at equal distances evolve towards an equilibrium relative configuration while the point particles collapse onto a single point in a finite time.